In Search of Religious Elements in the Dutch Nature Policy. (29th February 2016) - Jansen, Peter; Van Der Stoep, Jan; Keulartz, Jozef; Jochemsen, Henk
Abstract : The way people or organizations describe or depict nature conveys their view of nature. In the Dutch discourse, views of nature are mostly conceived as socio-cultural constructs regarding the character, value, and appreciation of nature. Views of nature tell us how we perceive nature and how we want to relate to it. Likewise, they shape our preferences for certain types of nature. Views of nature function as frames and provide an interpretive and remective context for our experiences with nature. Views of nature are also digestions of meaningful experiences. It is through communication that we become aware of such experiences. We argue that meaningful experiences have religious depth. On the basis of this argument any discourse on nature contains, in a sense, religious subtexts. We examine the Dutch discourse on nature.